Factors Affecting Entrepreneurial Intention of Indigenous Entrepreneurs of Bangladesh (Global Journal of Human-Social Science, 2023)
Globalization the technological revolution and the alleged climate crisis have brought about significant changes in the patterns of economic development experienced by humanity The evidence that human activities play an important role in environmental degradation is more evident Faced with this scenario of crises and uncertainties the economic sustainability of large corporations may be compromised by external issues over which societies have no control Much has been disclosed about the need for companies to seek the ability to generate value for the public in order to obtain higher levels of economic and environmental sustainability Within this perspective that corporations must be able to generate value and not just profits the present work is inserted The prospect that natural resources can be exploited in an exhaustive manner until they are exhausted in order to obtain maximum profits in business does not hold up corporate law increasingly turns to the need to develop its activities in a sustainable way both by economic and environmental bias
Keywords: entrepreneurial intentions; entrepreneurs; bangladesh; indigenous; indigenous entrepreneurs